Tip‐Induced Inversion of the Chirality of a Molecule's Adsorption Potential Probed by the Switching Directionality. Issue 12 (17th February 2020) - Bauer, Anja; Maier, Markus; Schosser, Werner M.; Diegel, Josefine; Paschke, Fabian; Dedkov, Yuriy; Pauly, Fabian; Winter, Rainer F.; Fonin, Mikhail
Abstract: The switching behavior of surface‐supported molecular units excited by current, light, or mechanical forces is determined by the shape of the adsorption potential. The ability to tailor the energy landscape in which a molecule resides at a surface gives the possibility of imposing a desired response, which is of paramount importance for the realization of molecular electronic units. Here, by means of scanning tunneling microscopy, a triazatruxene (TAT) molecule on Ag(111) is studied, which shows a switching behavior characterized by transitions of the molecule between three states, and which is attributed to three energetically degenerate bonding configurations. Upon tunneling current injection, the system can be excited and continuously driven, showing a switching directionality close to 100%. Two surface enantiomers of TAT show opposite switching directions pointing at the chirality of the energy landscape of the adsorption potential as a key ingredient for directional switching. Further, it is shown that by tuning the tunneling parameters, the symmetry of the adsorption potential can be controllably adjusted, leading to a suppression of the directionality or an inversion of the switching direction. The findings represent a molecule‐surface model system exhibiting unprecedented control of the shape of its adsorption potential. Abstract : The triazatruxene (TAT)/Ag(111) system represents a molecular three‐state switch, which, upon tunneling current injection, can be excited and continuously driven, showing a switching directionality close to 100%. It is shown that by tuning the tunneling parameters, a suppression of the directionality or an inversion of the switching direction can be achieved by adjusting the symmetry of the adsorption potential.